ANISOTROPIC CHANGES IN P-WAVE VELOCITY AND ATTENUATION DURING DEFORMATION AND FLUID INFILTRATION OF GRANITE - Stanchits S.A.; Lockner D.A.; Ponomarev A.V. (My University, 2003)
Fluid infiltration and pore fluid pressure changes are known to have a significant effect on the occurrence of earthquakes. Yet, for most damaging earthquakes, with nucleation zones below a few kilometers depth, direct measurements of fluid pressure variations are not available. Instead, pore fluid pressures are inferred primarily from seismic wave propagation characteristics such as V p/Vs ratio, attenuation and reflectivity contacts. We present laboratory measurements of changes in P-wave velocity and attenuation during the injection of water into a granite sample as it was loaded to failure. A cylindrical sample of Westerly granite was deformed at constant confining and pore pressures of 50 and 1 MPa respectively. Axial load was increased in discrete steps by controlling axial displacement. Anisotropic P-wave velocity and attenuation fields were determined during the experiment using an array of 13 piezoelectric transducers. At the final loading steps (86 and 95 percent of peak stress), both spatial and temporal changes in P-wave velocity and peak-to-peak amplitudes of P- and S-waves were observed. P-wave velocity anisotropy reached a maximum of 26%. Transient increases in attenuation of up to 483 dB/meter were also observed and were associated with diffusion of water into the sample. We show that velocity and attenuation of P-waves are sensitive to the process of opening of microcracks and the subsequent resaturation of these cracks as water diffuses in from the surrounding region. Symmetry of the orientation of newly formed microcracks results in anisotropic velocity and attenuation fields which systematically evolve in response to changes in stress and influx of water. With proper scaling, these measurements provide constraints on the magnitude and duration of velocity and attenuation transients that can be expected to accompany the nucleation of earthquakes in the earth's crust.